Defining a Dryland Grain Sorghum Production Function for the Central Great Plains. (1st July 2017) - Nielsen, David C.; Vigil, Merle F.
Abstract : Core Ideas: Grain sorghum water use/yield production function has a slope of 30.2 kg ha −1 mm −1 . Slope is greater than most other previously reported, but typical of C4 species. Production function can be used with precip record to estimate yield probability. Grain sorghum ( Sorghum bicolor L. Moench) is a drought‐tolerant C4 species capable of making use of limited available water supplies and is suitable for dryland crop rotations in the central Great Plains. In order for farmers to assess the production risk encountered when utilizing sorghum in rotations, a water use–yield production function would be useful. Previously published production functions vary widely in reported slope of the relationship between water use and grain yield, with many of those slopes being much less than expected for a C4 species. The objectives of this experiment were to determine a water use–yield production function applicable to grain sorghum grown in the central Great Plains and to use that production function with a long‐term precipitation record to assess production risk. Sorghum water use and yield data were collected from 2006 to 2016 at Akron, CO, and a production function was determined by linear regression to be yield (kg ha −1 ) = 30.2 × (water use [mm] – 259). A grain yield of at least 4000 kg ha −1 would be expected to occur 16% of the time if plant available soil water at planting was 111 mm and 92% of the time if 259 mm was available. Both the production function and the probability exceedance graphs will be useful to farmers in assessing production risk as they consider incorporating grain sorghum into dryland crop rotations in the central Great Plains.